2011
DOI: 10.1603/an10068
|View full text |Cite
|
Sign up to set email alerts
|

Tissues Involved in Sex Pheromone Production in Phyllophaga obsoleta (Coleoptera: Scarabaeoidea: Melolonthidae)

Abstract: Females of Phyllophaga obsoleta (Blanchard) (Coleóptera: Scarabaeoidea: Melolonthidae) perform "sexual calling" with their protractile genital chamber (PGC) exposed to release substances that attract males. Histological aspects of the PGC and accessory glands ( AGs) of P. obsoleta females were studied. Studies with light microscope and transmission electron microscope revealed exocrine tissue in the posterior section of the PGC, where it might be producing the attractants. This epithelial gland is formed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…For the monitoring and management of these beetle species, studies have been carried out to take advantage of the substances involved in intraspecific interactions [ 7 , 8 , 9 , 10 ], focusing on volatile organic compounds involved in attracting a partner for copulation, such as sex pheromones [ 11 , 12 ]. Bacteria have been observed in the reproductive system of females of Melolonthidae, specifically in the accessory glands and the genital chamber-structures associated with sex pheromones production [ 10 , 11 , 12 , 13 , 14 ]. Based on this evidence, it has been suggested that bacteria participate in the production of these chemicals, such as in the case of Morganella morganii found in the accessory glands of female individuals of melolonthid Costelytra zealandica beetles.…”
Section: Introductionmentioning
confidence: 99%
“…For the monitoring and management of these beetle species, studies have been carried out to take advantage of the substances involved in intraspecific interactions [ 7 , 8 , 9 , 10 ], focusing on volatile organic compounds involved in attracting a partner for copulation, such as sex pheromones [ 11 , 12 ]. Bacteria have been observed in the reproductive system of females of Melolonthidae, specifically in the accessory glands and the genital chamber-structures associated with sex pheromones production [ 10 , 11 , 12 , 13 , 14 ]. Based on this evidence, it has been suggested that bacteria participate in the production of these chemicals, such as in the case of Morganella morganii found in the accessory glands of female individuals of melolonthid Costelytra zealandica beetles.…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive apparatus of C. barrerai females has the general arrangement of the Melolonthidae [ 8 , 13 , 14 , 29 ]. The bursa copulatrix and the spermatheca connect to the genital chamber, storing and nourishing the sperm inside the female body until oviposition [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of microorganisms in lab-reared females indicates that these might be transferred by the mother or acquired during the larval period and not transferred by the male during mating. The architecture of the genital chamber and the presence of microorganisms suggest that they are relevant during attractant production [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations